Berteologi Kontekstual dari Mitos Plai Long Diang Yung - Yovinus Andi nata; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2022)
The focus of this study is on theological reflection on the myth of Plai Long Diang Yung which is contained in the culture of the Dayak Wehea people. This myth has a special and central place in the life of the local people and is the origin of the Lom Plai celebration which is the culmination of all traditional celebrations and rituals. This myth has an important meaning in people's lives and talks about many things related to human existence, nature and God. With this fact, the myth can become a locus theologic that can enrich the reflection of the Church's faith and root the faith in culture and culture in the light of faith. The method used in this paper is based on the results of critical reading of the mythical text of Plai Long Diang Yung and the Christian Tradition text. This study found that the myth of Plai Long Diang Yung contained a very rich theological meaning which spoke of Christ, salvation and God who is not limited to human sexuality.